Cancer Incidence and Survival Trends by Subtype Using Data from the Surveillance Epidemiology and End Results Program, 1992-2013 - Noone, Anne-Michelle; Cronin, Kathleen A; Altekruse, Sean F; Howlader, Nadia; Lewis, Denise R; Petkov, Valentina I; Penberthy, Lynne (Cancer epidemiology, biomarkers & prevention, 2017)
Cancers are heterogeneous, comprising distinct tumor subtypes. Therefore, presenting the burden of cancer in the population and trends over time by these tumor subtypes is important to identify patterns and differences in the occurrence of these subtypes, especially to generalize findings to the U.S. general population. Using SEER Cancer Registry Data, we present incidence rates according to subtypes for diagnosis years (1992-2013) among men and women for five major cancer sites: breast (female only), esophagus, kidney and renal pelvis, lung and bronchus, and thyroid. We also describe estimates of 5-year relative survival according to subtypes and diagnosis year (1992-2008). We used Joinpoint models to identify years when incidence rate trends changed slope. Finally, recent 5-year age-adjusted incidence rates (2009-2013) are presented for each subtype by race and age. Hormone receptor-positive and HER2-negative was the most common subtype (about 74%) of breast cancers. Adenocarcinoma made up about 69% of esophagus cases among men. Adenocarcinoma also is the most common lung subtype (43% in men and 52% in women). Ninety percent of thyroid subtypes were papillary. Distinct incidence and survival patterns emerged by these subtypes over time among men and women. Histologic or molecular subtype revealed different incidence and/or survival trends that are masked when cancer is considered as a single disease on the basis of anatomic site. Presenting incidence and survival trends by subtype, whenever possible, is critical to provide more detailed and meaningful data to patients, providers, and the public. .